2016
DOI: 10.1002/dev.21432
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of object‐in‐context and object‐place‐context recognition in the developing rat

Abstract: Since the seminal report on novel object recognition in the rat (Ennaceur & Delacour, 1988), novelty recognition paradigms have become increasingly prevalent in learning and memory research. Novelty recognition tasks do not require extensive training or complex behaviors, and thus are especially suitable for studying the ontogeny of various forms of memory (e.g., object, spatial, and contextual memory). However, relatively little is known about the determinants of recognition memory during development. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 45 publications
6
28
3
Order By: Relevance
“…Recognition memory depends on mature mPFC‐hippocampus and hippocampal‐entorhinal cortex circuitry . The maturation of this circuitry, which in healthy mice appears to parallel the maturation of mPFC glutamatergic innervation (around the age of P30 in rodents), was previously exemplified by late onset of the ability to perform a task . In males, both the maternal and offspring Mthfr genotypes contributed to memory impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Recognition memory depends on mature mPFC‐hippocampus and hippocampal‐entorhinal cortex circuitry . The maturation of this circuitry, which in healthy mice appears to parallel the maturation of mPFC glutamatergic innervation (around the age of P30 in rodents), was previously exemplified by late onset of the ability to perform a task . In males, both the maternal and offspring Mthfr genotypes contributed to memory impairment.…”
Section: Discussionmentioning
confidence: 99%
“…NOR is mediated in part by the hippocampus. Most evidence supports a role for N‐methyl‐D‐aspartate ‐ receptor (NMDA‐R) in mediating novelty recognition; however, there are conflicting data . We did not assess NMDA‐R levels here.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that NMDARs are involved in learning tasks during the pre‐weanling period of development (Highfield, Nixon, & Amsel, ; Langton, Kim, Nicholas, & Richardson, ; Lincoln, Coopersmith, Harris, Cotman, & Leon, ). The role of NMDARs in learning and memory has been previously examined by our lab in developmental studies of the CPFE (Heroux et al, ; Schiffino et al, ) and various hippocampal‐dependent object recognition tasks (Jablonski, Schreiber, Westbrook, Brennan, & Stanton, ; Ramsaran, Sanders, & Stanton, ); as well as T‐maze working memory and reversal tasks (Chadman, Watson, & Stanton, ; Watson, Herbert, & Stanton, ; Watson & Stanton, ). In the CPFE, systemic NMDAR antagonism during context preexposure or training phases disrupts retention test freezing in PD24 and PD31 rats (Burman, Murawski, Schiffino, Rosen, & Stanton, ; Heroux et al, ).…”
Section: Discussionmentioning
confidence: 99%